Image complexation in the following coordinator of homing head to improve shooting efficiency of anti-aircraft missile system type «Strela-10M2» - D. S. Sharak; A. Yu. Liplianin; A. V. Khizhniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The application of visible and infrared images integration in tracking target of the homing head (HH) to improve the shooting efficiency of anti-aircraft missile system (AAMS) type «Strela-10M2» is substantiated. A variant to reduce the firing cycle of AAMS by eliminating the fact of switching operating modes is presented. It's shown the dependence of likelihood of fire mission execution by a subunit armed with AAMS as a function of the image quality of the accompanied target characterized by a standard deviation of pixel brightness in the tracking monitor of the HH.